Health Professionals' Communication Competences as a Light on the Patient Pathway - Vaz de Almeida, Cristina (2021)
This article proposes a three-factor model of communication competencies inspired in literature review and evaluated and completed by Portuguese health specialists with expertise on health literacy, who were organized into four focus groups (n=25). The study includes a response to the lack of consensus in the literature as to what specific and operative competencies the health professional should perform in clinical encounters with the patients. All the participants in the focus group agreed and reinforced that an aggregated and interdependent model, which is composed of assertiveness, clarity of language, and positivity (ACP model), can be an effective health communication model.